Aerodynamic Optimization of Horizontal Axis Wind Turbine Blades Using Winglet and Spoiler Add-Ons: A CFD Study - Oluwaseyi Omotayo Alabi; Adeoti Oyegbori Laoye; Saidat Abisoye Salisu (Scientific Journal of Engineering Research, 2026)
The aerodynamic performance of wind turbine blades plays a critical role in maximizing energy generation and overall system efficiency, making it a key consideration in modern renewable energy design. Despite extensive research on blade optimization, there remains a notable gap in understanding the combined effects of spoiler and winglet geometries, particularly their size and orientation on aerodynamic efficiency under low wind speed conditions. This study aims to address this gap by conducting a comprehensive numerical investigation into the influence of spoiler and winglet configurations on wind turbine performance. Computational Fluid Dynamics (CFD) simulations were performed using COMSOL Multiphysics, with the k-ε turbulence model employed to accurately capture turbulent flow behavior. A detailed parametric analysis was carried out, considering winglet height (4%–13% of blade radius), cant angle (20°–90°), twist angle (−2° to 12°), and tip speed ratio (0.02–1.12) at a wind velocity of 3 m/s. The results reveal that optimal combinations of spoiler and winglet parameters significantly enhance aerodynamic efficiency. The study identifies specific design ranges that maximize power output, achieving a peak aerodynamic power of 62.8 W. Although the addition of these aerodynamic devices increases the inertia of the turbine, the system performance improves, with an observed increase in output power of approximately 12%. These findings provide valuable insights for the design and optimization of wind turbine blades, particularly for low wind speed applications.